Assessing the vegetation and soil microbial ecology of renosterveld rangelands around Nieuwoudtville, Northern Cape Province - Solomon, Gabrielle Marie (University of the Western Cape, 2016)
Magister Scientiae (Biodiversity and Conservation Biology) - MSc (Biodiv and Cons Biol) === The Bokkeveld Plateau, a region hosting high plant endemism, is home to two arid mountain centre renosterveld types. One, Nieuwoudtville Shale Renosterveld, has partially been transformed into croplands and pastures, with about 40 % remaining as non-contiguous fragments on privately owned land, and is used as natural rangelands for sheep grazing. The vegetation, soil chemical parameters, and rhizosphere soil microbial ecology of a dominant plant, Eriocephalus purpureus, were assessed. A combination of field sampling and recording, laboratory analyses of soil samples, and interviews were used to glean data. Data were statistically analysed using multivariate techniques. Overall plant species richness did not differ among the study sites, though plant species richness and cover of the different plant growth form categories varied among the sites. Soil chemical parameters varied among sites. Soil chemical and rhizosphere soil microbial parameters co-varied, and showed different profiles among the study sites. High cover of E. purpureus was associated with high microbial enzyme activity, while high cover of (other, non-dominant) non-succulent shrubs was associated with high bacterial functional diversity. Cover of geophytes, Asparagus capensis and perennial grass was associated with high microbial biomass. The findings indicate that E. purpureus-dominated Niewoudtville Shale Renosterveld is heterogeneous not only in terms of vegetation, but also in terms of soil chemical and microbial parameters. The results support the conservation of all fragments of remaining renosterveld, as they may serve as valuable resources of not only plant genetic material but also of soil microbial communities.